Molecular niobium(v) complexes with mononuclear Nb1 and dinuclear oxo species Nb2O connected through aryl di- or tetra-carboxylate linker. Issue 33 (5th August 2022) - Andriotou, Despoina; Duval, Sylvain; Trivelli, Xavier; Volkringer, Christophe; Loiseau, Thierry
Abstract : Di- or tetracarboxylic acid ligands were used to isolate molecular coordination complexes containing the association of several mononuclear Nb1 moiety and dinuclear Nb2 O niobium(v ) polyoxo clusters. Abstract : Several aryl polycarboxylic ligands (pyromellitic acid, 4, 4′-azobenzenedicarboxylic acid and 3, 3′, 5, 5′-azobenzenetetracarboxylic acid) have been used to react with the pentavalent ethoxide niobium(v ) precursor Nb(OEt)5 . Three new crystalline molecular compounds (1 with pyromellitate, 2 with 4, 4′-azobenzenedicarboxylate and 3 with 3, 3′, 5, 5′-azobenzenetetracarboxylate) were isolated from slow crystallization at room temperature from the mother liquid containing the precursor Nb(OEt)5 . They are composed of one polycarboxylate ligand fully coordinated to mononuclear or dinuclear octahedrally-coordinated niobium(v ) units. For the dimers, the two adjacent niobium centers are bridged by one μ-O and one μ-OEt groups and complexed by only one of the syn – syn bidentate carboxylate function arms from the polytopic ligand. Compounds 1–3 were characterized in solid state by single-crystal and powder X-ray diffraction analysis. Insight into the formation of the three compounds was supported by the help of infrared and liquid 1 H NMR spectroscopy.